2021
DOI: 10.1093/genetics/iyab122
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic mating in outbred species: predicting cross usefulness with additive and total genetic covariance matrices

Abstract: Diverse crops are both outbred and clonally propagated. Breeders typically use truncation selection of parents and invest significant time, land and money evaluating the progeny of crosses to find exceptional genotypes. We developed and tested genomic mate selection criteria suitable for organisms of arbitrary homozygosity level where the full-sibling progeny are of direct interest as future parents and/or cultivars. We extended cross variance and covariance variance prediction to include dominance effects and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 65 publications
4
44
0
Order By: Relevance
“…The results presented in the underlying study largely correspond to ndings obtained from a cassava breeding program (Wolfe et al 2021). In cassava, median prediction abilities for the usefulness criterion predicted by the UFC ranged from 0.1 to 0.83 in a cross-validated scenario and 95% of the prediction abilities were greater than zero, assuming a heritability of h 2 = 1 and varying selection intensities per family.…”
Section: Prediction Of the Usefulnesssupporting
confidence: 78%
See 2 more Smart Citations
“…The results presented in the underlying study largely correspond to ndings obtained from a cassava breeding program (Wolfe et al 2021). In cassava, median prediction abilities for the usefulness criterion predicted by the UFC ranged from 0.1 to 0.83 in a cross-validated scenario and 95% of the prediction abilities were greater than zero, assuming a heritability of h 2 = 1 and varying selection intensities per family.…”
Section: Prediction Of the Usefulnesssupporting
confidence: 78%
“…In cassava, median prediction abilities for the usefulness criterion predicted by the UFC ranged from 0.1 to 0.83 in a cross-validated scenario and 95% of the prediction abilities were greater than zero, assuming a heritability of h 2 = 1 and varying selection intensities per family. Wolfe et al (2021) similarly described low differences between the prediction abilities for the family mean and the UFC and reported a high correlation of both.…”
Section: Prediction Of the Usefulnessmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite an increasing number of publications proposing to predict the family mean and variance for a specific cross based on marker effects, proof of concepts based on comprehensive data sets are scarce. A recent attempt used a dataset from a cassava breeding program and yielded disappointing results [ 18 ]. In our study, we investigated the potential and limitations of predicting the UFC to identify optimal parent combinations using a data set generated in the course of commercial winter barley breeding.…”
Section: Discussionmentioning
confidence: 99%
“…All the aforementioned studies showed very promising results but assumed that marker effects were known [ 10 , 11 , 12 , 14 , 15 , 16 ] or estimated marker effects considering genomic and phenotypic data of the populations whose UFC should be predicted [ 17 ]. In a study on cassava [ 18 ], marker effects and UFC were estimated in separate training and testing populations, yielding disappointing results.…”
Section: Introductionmentioning
confidence: 99%